Are periods of feeding and fasting protective during critical illness?. Issue 2 (2nd March 2021) - Puthucheary, Zudin; Gunst, Jan
Abstract : Purpose of review: To review the mechanisms how intermittent feeding regimens could be beneficial in critically ill patients. Recent findings: Large randomized controlled trials (RCTs) have failed to demonstrate consistent benefit of early, enhanced nutritional support to critically ill patients, and some trials even found potential harm. Although speculative, the absence of a clear benefit could be explained by the continuous mode of feeding in these trials, since intermittent feeding regimens had health-promoting effects in healthy animals and humans through mechanisms that also appear relevant in critical illness. Potential protective mechanisms include avoidance of the muscle-full effect and improved protein synthesis, improved insulin sensitivity, better preservation of circadian rhythm, and fasting-induced stimulation of autophagy and ketogenesis. RCTs comparing continuous versus intermittent feeding regimens in critically ill patients have shown mixed results, albeit with different design and inclusion of relatively few patients. In all studies, the fasting interval was relatively short (4–6 h maximum), which may be insufficient to develop a full fasting response and associated benefits. Summary: These findings open perspectives for the design and clinical validation of intermittent feeding regimens for critically ill patients. The optimal mode and duration of the fasting interval, if any, remain unclear.